(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2023)
In compliance with the substantive functions "Education, Research, Extension" and the responsibility with the protection of the environment and the sustainable development of the country, University Social Responsibility and environmental management have become aspects of great significance for Higher Education Institutions (HEI). Thus, taking into account the rapid environmental deterioration and the unfavorable interaction of human beings with their environment and according to the commitment that universities have with the communities and their social environment, HEIs have been implementing actions leading to the care of the environment seeking to transform their relationships and achieve a balance between the university and the community. From this perspective and through a descriptive documentary review methodology, this research focuses on the analysis of studies carried out in recent years by theoreticians in different databases, about the good practices of university social responsibility in the environmental dimension, where the results allowed identifying the challenges and impacts of environmental management in compliance with the RSU, on the other hand, it was determined that the issues of environmental care and sustainability should be worked holistically and should not be isolated from the university work, seeking to consolidate an environmental culture; On the other hand, the review of background information indicated the need to build permanent spaces to encourage the intervention of the communities in activities and projects that involve internal and external groups that are part of the universities.